The Strategic Construction of Aryan Identity of Brokpas: An Anthropological Perspective. Issue 1 (June 2022) - Chakraborty, Mainak; Mitra, Santanu; Harashawaradhana,
The Brokpa community of India is the most celebrated tribal population of the country. This population is not only a major attraction of Ladakh, but also their villages are must visit destination of this country for foreign travellers. The reason of this interest is Brokpas 'Aryan' identity and the status of 'pure' attached to them. This identity or essence of Brokpa was created strategically and is more of a cultural identity than racial. Even there is no genetical evidence of their Indo-European descent. This article will discuss about the construction of Aryan identity of Brokpa from outside and inside the community, and this identity is affecting the population.